The Application of Analytic Hierarchy Process (AHP) in the Selection of Type and Location of Water Treatment Plant - Arash Shahmansouri; Mohammad Salman Sabahi; Reza Rezaei Adryani; Ali Lotfi; Ahmad Khodadadi Darban (آب و فاضلاب, 2012)
Several factors affect the selection of water and wastewater treatment plants’ location. Each factor, depends on the site situation, has different weight in decision making process. The object of this study was to investigate the application of analytic hierarchy process (AHP) in the selection of type and location of water treatment plant. In the first step of the study, two alternatives, including building a centralized treatment plant and domestic plants for different places, were assessed. Alternatives were ranked with four parameters from their preference point of view. Results suggested that the centralized water treatment plant was the more preferred choice. In the second step, selection of the plant location was performed using fourteen parameters for different locations. Because of the importance of economic issues in site selection, an index named “value index” was defined and calculated for each location. The final decision was made based on this index.